Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1007/s00198-014-2791-5
|View full text |Cite
|
Sign up to set email alerts
|

Strontium potently inhibits mineralisation in bone-forming primary rat osteoblast cultures and reduces numbers of osteoclasts in mouse marrow cultures

Abstract: SummaryThe basic mechanisms by which strontium ranelate acts on bone are still unclear. We show that an important action of strontium salts is to block calcification in cultures of osteoblasts, the bone-forming cells. These results suggest that strontium treatment could have previously overlooked effects on bone.IntroductionThe basic mechanisms of action of strontium ranelate (SrR) on bone have remained unclear. We studied the direct actions of Sr2+ salts in functional cultures of osteoblasts and osteoclasts.M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
22
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 42 publications
4
22
0
1
Order By: Relevance
“…For the loading of Sr, several studies have indicated that Sr can mainly improve the biological response of host bone for the following reasons: first, Sr can improve the biological response of bone through enhanced osteoblast differentiation by increasing many osteoblast markers (eg, ALP, COL‐1, bone sialoprotein, and OCN) . Second, Sr can improve the biological response of bone through inhibition of osteoclast function by decreasing functional expression of osteoclast markers and disrupting the cytoskeleton, which is essential for the resorbing activity of osteoclasts . Third, Sr loaded on the titanium surface can release to the implant‐tissue interface locally and directly, thus enabling effective absorption by bone tissues around the implant, which promotes bone formation and suppresses bone resorption …”
Section: Discussionmentioning
confidence: 99%
“…For the loading of Sr, several studies have indicated that Sr can mainly improve the biological response of host bone for the following reasons: first, Sr can improve the biological response of bone through enhanced osteoblast differentiation by increasing many osteoblast markers (eg, ALP, COL‐1, bone sialoprotein, and OCN) . Second, Sr can improve the biological response of bone through inhibition of osteoclast function by decreasing functional expression of osteoclast markers and disrupting the cytoskeleton, which is essential for the resorbing activity of osteoclasts . Third, Sr loaded on the titanium surface can release to the implant‐tissue interface locally and directly, thus enabling effective absorption by bone tissues around the implant, which promotes bone formation and suppresses bone resorption …”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the effects of strontium ranelate on alveolar bone metab- and number, some investigations failed to observe any effect of this medication on osteoblast numbers and indicated that strontium ranelate inhibits mineralization and decreases collagen cross-linking in bone. 38,39 Based on the current immunohistochemical findings, it is hypothesized that most of the histometric benefits induced by strontium ranelate on ligature-induced bone resorption rely on its anti-resorptive rather than its anabolic action. Therefore, the dual effects of strontium ranelate might be not verified under an infectiousinflammatory state and this medication may present differences in the mode of its action according to different environmental factors influencing bone metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Nardone et al reported that Sr 2+ with different concentrations revealed the biphasic action of mineralization in vitro. Wornham et al demonstrated that Sr 2+ inhibited bone formation, especially the mineralization. In our study, we observed that the OPN gene expressions were upregulated for dozens of times when exposed to Sr 2+ .…”
Section: Discussionmentioning
confidence: 99%